2016
DOI: 10.3892/mmr.2016.5437
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of Beclin-1 is significantly associated with a poor prognosis in oral tongue squamous cell carcinoma

Abstract: The autophagy-related gene Beclin-1 is critical in the regulation of tumourigenesis and progression, but its role in oral tongue squamous cell carcinoma (OTSCC) has not yet been reported. This study aimed to investigate Beclin-1 expression and its significance in OTSCC. Beclin-1 expression was assessed by reverse transcription-quantitative polymerase chain reaction or western blot analysis in 14 OTSCC tissues and matched adjacent noncancerous tissues as well as in 5 OTSCC cell lines and a normal tongue epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Meanwhile, our previous studies showed that the expression level of Bcl-xl was reduced in DHA-treated Cal-27 cells [ 8 ]. Consistently, one clinical study showed that Beclin-1 acted as a tumor suppressor in the development or progression of TSCC [ 37 ].…”
Section: Discussionmentioning
confidence: 64%
“…Meanwhile, our previous studies showed that the expression level of Bcl-xl was reduced in DHA-treated Cal-27 cells [ 8 ]. Consistently, one clinical study showed that Beclin-1 acted as a tumor suppressor in the development or progression of TSCC [ 37 ].…”
Section: Discussionmentioning
confidence: 64%
“… 34 The prognostic role of Beclin-1 was investigated in various types of cancers, but the conclusions were inconsistent. It was shown by some studies that high level of Beclin-1 predicted a better outcome in colorectal carcinoma, 35 oral carcinoma, and multiple myeloma, 36 , 37 while other researchers showed that high level of Beclin-1 was correlated with a worse outcome in certain cancers such as endometrial carcinoma and nasopharyngeal carcinoma. 38 , 39 Moreover, some researches showed that Beclin-1 was not associated with prognosis of cancers.…”
Section: Discussionmentioning
confidence: 99%
“… 77 In TSCC cells, Beclin 1 expression in 14 TSCC tissues and five TSCC cell lines detected by RT-PCR and Western blotting was significantly decreased. 78 Beclin 1 expression detected by IHC was also decreased in 133 TSCC specimens. The decreased expression of Beclin 1 was associated with poor differentiation, lymph node metastasis, advanced clinical TNM, and a poor five-year overall survival.…”
Section: Beclin 1 and Head And Neck Cancersmentioning
confidence: 95%